ANALISIS SISTEM PENGENDALIAN INTERNAL PIUTANG USAHA PADA PT. HASJRAT ABADI TOYOTA CABANG MANADO - Tahumang, Sulasry; Ilat, Ventje; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
PT Hasjrat Abadi Toyota Manado Branch is one representative offline from Toyota in North Sulawesi Province and become a representative that sell car in cash or credit in Manado City and make its’ agents obtain people to choose for purchasing car in credit, sales credit account will generate receivables in corporate bookkeeping. Accounts receivable commensurate terms or grace period against payment since the surrender of goods trading companies.The purpose of this study to analyze the internal control system receivables at PT Hasjrat Abadi Toyota Manado Branch. Research type in this research is descriptive research. Research’s result shows that internal controlling of account receivable in PT Hasjrat Abadi Toyota Manado Branch has been applied well, based on Control Environment, Risk Determination, Control Activities, Communication Information, Supervising and Monitoring. Branch Manager and employees of PT Hasjrat Abadi Toyota Manado Branch supposed to deliberate internal controlling system of account receivables that already perform well and looking for new breakthrough in implementation of system in this dealer.Keywords : internal control system, account receivable.